2020
DOI: 10.3390/nu12071966
|View full text |Cite
|
Sign up to set email alerts
|

Phytopharmacological Possibilities of Bird Cherry Prunus padus L. and Prunus serotina L. Species and Their Bioactive Phytochemicals

Abstract: Wild cherry is a plant observed in the form of trees or shrubs. This species comprises about twenty kinds of plants and the most popular are two, Prunus padus L. and Prunus serotina L., whose properties and content of phytochemical compounds are subject to studies. Wild cherry contains many active compounds, including tocopherols, vitamins, polyphenols and terpenes, which can have beneficial effects on health. On the other hand, wild cherry contains cyanogenic glycosides. Nevertheless, current research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 125 publications
2
8
0
Order By: Relevance
“…Natural drugs have been successfully utilized by the scientific community for the discovery of new drugs and have exhibited far‐reaching impact in the field of chemicobiology 54–56 . The qualitative and quantitative analysis of chloroform extract of leaves of T. pallida revealed the presence of polyphenols, flavonoids, lipids and proteins, which in accordance with the previous studies are excellent therapeutic agents against various deadly diseases 57–61 . The UV–visible profile showed the characteristic peaks of phenols, flavonoids, and alkaloids 62,63 in the UV region and predicted the presence of terpenoids, chlorophyll, and tannins in the visible region 63,64 .…”
Section: Discussionsupporting
confidence: 79%
“…Natural drugs have been successfully utilized by the scientific community for the discovery of new drugs and have exhibited far‐reaching impact in the field of chemicobiology 54–56 . The qualitative and quantitative analysis of chloroform extract of leaves of T. pallida revealed the presence of polyphenols, flavonoids, lipids and proteins, which in accordance with the previous studies are excellent therapeutic agents against various deadly diseases 57–61 . The UV–visible profile showed the characteristic peaks of phenols, flavonoids, and alkaloids 62,63 in the UV region and predicted the presence of terpenoids, chlorophyll, and tannins in the visible region 63,64 .…”
Section: Discussionsupporting
confidence: 79%
“…Various studies have shown that almond by-products (of the kernel, skin, and shell) contain bioactive compounds such as phenolic compounds (flavonoids and phenolic acids) and terpenoids (sterols and triterpenoids), whose composition and quantity depend on factors such as the geographical distribution, origin, environmental conditions, exposure to pests, UV radiation, harvest maturity and obtaining and extraction process (10)(11)(12)(13)(14). These by-products are a source of potent antioxidants for the control of oxidative processes, natural antimicrobials, prebiotic and antiviral compounds (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Historical reports and centuries-old cultural traditions show that some plants can be an alternative to standard pharmacotherapy or, at least, help with treatment or have a preventative effect. Modern science is very eager to verify these properties by analyzing the so-called medicinal plants for the presence of valuable bioactive compounds, including antioxidants, and the resulting interesting potential health properties [6][7][8][9][10][11][12][13][14]. In order for them to be introduced into the diet, their purity in terms of toxic compounds must also be taken into account [15,16].…”
Section: Introductionmentioning
confidence: 99%